Technomodern poetics : the American literary avant-garde at the start of the Information Age - Tietchen, Todd F. (New American canon., 2018)
"After the second World War, the term "technology" came to signify both the anxieties of possible annihilation in a rapidly changing world and the exhilaration of accelerating cultural change. Technomodern Poetics examines how some of the most well-known writers of the era described the tensions between technical, literary, and media cultures at the dawn of the Digital Age. Poets and writers such as Allen Ginsberg, Charles Olson, Jack Kerouac, and Frank O'Hara, among others, anthologized in Donald Allen's iconic The New American Poetry, 1945-1960, provided a canon of work that has proven increasingly relevant to our technological present. Elaborating on the theories of contemporaneous technologists such as Norbert Wiener, Claude Shannon, J.C.R. Licklider, and a host of noteworthy others, these artists express the anxieties and avant-garde impulses they wrestled with as they came to terms with a complex array of issues raised by the dawning of the nuclear age, computer-based automation, and the expansive reach of electronic media. As author Todd Tietchen reveals, even as these writers were generating novel forms and concerns, they often continued to question whether such technological changes were inherently progressive or destructive. With an undeniable timeliness, Tietchen's book is sure to appeal to courses in modern English literature and American studies, as well as among fans of Beat writers and early Cold War culture"--